2004
DOI: 10.1002/cne.20200
|View full text |Cite
|
Sign up to set email alerts
|

Branched‐chain amino acids and neurotransmitter metabolism: Expression of cytosolic branched‐chain aminotransferase (BCATc) in the cerebellum and hippocampus

Abstract: In the brain, catabolism of the branched-chain amino acids (BCAAs) provides nitrogen for the synthesis of glutamate and glutamine. Glutamate is formed through transfer of an amino group from BCAA to alpha-ketoglutarate in reaction catalyzed by branched-chain aminotransferases (BCAT). There are two isozymes of BCAT: cytosolic BCATc, which is found in the nervous system, ovary, and placenta, and mitochondrial BCATm, which is found in all organs except rat liver. In cell culture systems, BCATc is found only in ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
71
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 80 publications
(75 citation statements)
references
References 47 publications
4
71
0
Order By: Relevance
“…The transamination of α-ketoglutarate to glutamate using BCAA-derived nitrogen occurs despite the diminution of BCATc expression. However, as BCATc is found primarily in the synaptic terminals (27), and it is not the ratelimiting step in BCAA metabolism, it is ideally positioned to use exogenous BCAAs for the synthesis of glutamate.…”
Section: Discussionmentioning
confidence: 99%
“…The transamination of α-ketoglutarate to glutamate using BCAA-derived nitrogen occurs despite the diminution of BCATc expression. However, as BCATc is found primarily in the synaptic terminals (27), and it is not the ratelimiting step in BCAA metabolism, it is ideally positioned to use exogenous BCAAs for the synthesis of glutamate.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, we identified (with at least 3 peptides) 23 proteins with significantly increased (Table 1) and 23 proteins with decreased ( Table 2) (1) - (Chihara et al, 2007), (2) - (Folci et al, 2014), (3) - (Chen et al, 2002), (4) - (Tanaka et al, 2000), (5) - (Ding and Shen, 2008), (6) - (Na et al, 2012), (7) - (Lyon et al, 2007), (8) - (Sweatt et al, 2004), (9) - (Bahn et al, 2002), (10) - (Manya et al, 1998), (11) - (Kamada et al, 2003), (12) - (McKenna et al, 2000), (13) - (Christel et al, 2012), (GO) -According to Gene Ontology database. …”
Section: Functional Clusters Of Altered Proteinsmentioning
confidence: 66%
“…BCAT1 is localized exclusively in neurons in the adult rat brain and catalyzes the reversible transamination of α-ketoglutarate to glutamate while GAD catalyzes the decarboxylation of glutamate to GABA (Sweatt et al, 2004). GABA degradation has an important role in glutamate-and GABA-erg balance and generates succinic semialdehyde (SSA) intermediate via the activation of GABA transaminase (GABA-T).…”
Section: Chronic Cerebral Hypoperfusion Effects On Gabaergic / Glutammentioning
confidence: 99%
“…For detection of phospho-E1␣, E1␣, and E2, an anti-E1␣ pS293, an anti-E2, and an E1␣ peptide antibody (27) were used. BCAT isozyme-specific antisera were raised in rabbits using purified recombinant human BCATm and BCATc and affinity purified as described (8,24). CsA was purchased from Enzo Life Sciences (Farmingdale, NY) and dissolved in dimethyl sulfoxide, rapamycin was purchased from LC Laboratories (Woburn, MA), NALA was purchased from BACHEM (Bubendorf, Switzerland).…”
Section: Methodsmentioning
confidence: 99%